Seasonal and decadal variability of hydrodynamics, sediment dynamics and morphological features at a non-tidal river delta coast - Sahin, Cihan; Guner, H. Anil Ari; Ozturk, Mehmet; Yuksel, Yalcin; Guner, Kerem (ELSEVIER, 2025)
The evolution of a deltaic coastline is affected by the interaction between the river flow and sediment supply, and the distribution of sediments by waves and tidal currents. The purpose of this study is to investigate the hydro-sedimentary processes in a vulnerable non-tidal river delta coast on a seasonal and decadal timescale. The Sakarya River delta coast locally experiences significant coastal retreat related to the energetic wave climate and anthropogenic factors, e.g., decrease of sediment discharge to the coast due to large volume reservoirs along river stream, construction of coastal structures accelerating coastal erosion, and regular dredging activities. Seasonal variability in hydrodynamics and sediment dynamics was investigated using three shipboard surveys (in February, July, and November 2019) conducted in the vicinity of the Sakarya River region of influence, covering different meteorological and hydrological conditions, and therefore allowing for observations under different forcing conditions. The field observations include vertical profiles of salinity, turbidity and temperature, collection of water and bottom sediment samples, and river cross-sectional measurements. The long-term variability of the coastline was analyzed using satellite images and the LITLINE numerical model based on a one-line theory, which was calibrated using satellite data. The field measurements indicate strong seasonal variability in hydrodynamics and sediment dynamics. In winter, freshwater extends offshore for similar to 1.5 km from the river mouth with SSC values exceeding 0.16 g/L. High bottom shear stresses induced by strong currents cause the erosion of the river bed, increasing the river depth. In the low-flow seasons, the impact distance of the river flow decreased to similar to 1 km and the amount of sediment carried by the river dropped to one-third of the value in winter. The river's carrying capacity decreases due to reduced river discharge by 75 to 80% compared to winter; therefore, fine material in suspension settles and depth decreases. The deposition of the sediments supplied by the river and the distribution of sediments by waves from west to east result in the accumulation of sand in the river mouth that leads to a decrease in the width of the river mouth from about 100 m (in February) to 20 m (in November). The LITLINE numerical model that was run between 1980 and 2019 indicates a yearly average accretion of +4.2 m at the west of the river mouth, supporting the field observations. Unlike the field observations and numerical model results, the satellite images indicate significant erosion of around-280 m at the west of the mouth of the Sakarya River between 1980-2015. The results reveal that regular dredging operations conducted at the river mouth play an important role in the erosion at the west of the mouth.
Keywords: Delta coast; Sediment dynamics; Shoreline evolution; Sakarya River; Hydrodynamics; TRANSPORT; DISCHARGE; ESTUARY; EROSION; Geology; Marine & Freshwater Biology; Oceanography